TO DETERMINE THE IMPORTANCE OF AGE AND SEX IN THE CLINICAL PRESENTATION AND SUBSEQUENT OUTCOME IN CHOLILITHIASIS. - Nazim Hayat; Badar-u-Duja (Journal of University Medical & Dental College, 1970)
ABSTRACT Objectives: To determine the importance of age and sex in patients of gall stone disease and surgical complications. Place and duration of Study: Department of surgery Madina Teaching Hospital Faisalabad. Period: Jan, 2012 to Oct 2012. Methodology: Data was obtained by standard data collection Proforma. All patients of gall stone disease admitted in surgical ward and operated on elective list were included. Males and females were divided into different groups with age less and more than 25 years. Outcomes of surgery in both sex and age groups recorded. Study Design: Observational study. Results: Total number of patients were 200.Male to female ratio was 5:1. Twenty two (11%) were of less than 25 years and 178(89%) were more than 25 years. One hundred forty three patients (71.5%) were symptom free at the time of presentation and they underwent laparoscopic cholecystectomy. Fifty seven(28.5%) presented with acute cholecystitis and given conservative trial before definitive surgery. Superficial wound infection was found to be the commonest complication. Conclusion: Incidence of gall stone is increasing in young and male patients. The rate of complications and conversion to open cholecystectomy is more in males as compared to females but it can be decreased with good patient selection, better preparation, understanding of the disease and surgical skills.